Sonogashira reaction cum cyclization under microwave irradiation supported by sodium aluminate (NaAlO2) and catalyzed by zinc: A green alternative approach in production of furo[3, 2-h]quinolones. (2023) - Saha, Pritam; Mukherjee, Koushik
Abstract: The Sonogashira reaction, characterized by the "formation of CC bond through cross-coupling a vinyl or aryl halide with an alkyne which is usually terminal, " is undoubtedly-one of the most expeditious and prompt reactions in chemical synthesis. The reaction conventionally employs palladium as a catalyst. In addition, co-catalyst such as copper species and an amine or phosphine is generally used. The chemical process takes place in moderate conditions, such as in an aqueous solution, usually at RT, and in the occurrence of mild bases. The reaction is employed to synthesize an array of beneficial products such as heterocycles, mimics of natural products, complex molecules with biological roles, nanomaterials, and above all, synthetic drugs. However, in this study, we aimed to execute this popular reaction using Sodium Aluminate (NaAlO2 ) as a base and solid support. The reaction is carried out with microwave irradiation using zinc as a catalyst. Therefore, this protocol eliminates the need for a catalyst as palladium, copper as a co-catalyst, and phosphines or amine as a base. These modifications make reactions more atom-friendly and implement green chemistry principles. In this connection, we developed newer energy, cost, and time-efficient etiquette for coupling following the cyclization of acetylenic derivative 8-quinolinols produced in situ by the microwave-based Sonogashira reaction. These essential methodology replacements helped us achieve an affordable and clean-energy synthesis protocol.